Nuclear receptors in regulation of bile acids transport and metabolism - A. F. Sheptulina; Ye. N. Shirokova; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. Nuclear receptors are ligandactivated transcription factors, involved in regulation of metabolism and transport of bile acids (BA) both under physiological, and cholestatic conditions. Accumulation of BA and other bile components in hepatocytes during cholestatic liver diseases is accompanied by liver cells damage and ready to fibrosis and cirrhosis. This article is devoted to the above-mentioned issues.Key points. Some adaptive processes including change of hepatocyte transport systems expression reduction of BA synthesis, activation of BA detoxication and elimination are upredgulated during cholestasis. All listed mechanisms are directed to minimize damage hepatocytes and nuclear receptors play the main role in their regulation. Nevertheless, realization of these adaptive processes, apparently, is insufficient to prevent cholestatic liver diseases.Conclusion. Accumulation of data on metabolism and transport of BA under physiological and cholestatic conditions allows not only to explain the mechanism of action of the drugs empericaly utilized for treatment of cholestasis for many years, but also to develop new, probably, more effective pharmaceuticals. So, it is supposed, that application of nuclear receptor ligands will help to boost hepatocyte protection mechanisms, and, hence, to slow down or arrest progression of disease.